Small molecules inhibiting the nuclear localization of YAP/TAZ for chemotherapeutics and chemosensitizers against breast cancers - Yusuke Oku; Naoyuki Nishiya; Toshiya Shito; Reiichiro Yamamoto; Yasufumi Yamamoto; Chihiro Oyama; Yoshimasa Uehara (FEBS Open Bio, 2015)
YAP and TAZ oncoproteins confer malignancy and drug resistance to various cancer types. We screened for small molecules that inhibit the nuclear localization of YAP/TAZ. Dasatinib, statins and pazopanib inhibited the nuclear localization and target gene expression of YAP and TAZ. All three drugs induced phosphorylation of YAP and TAZ, and pazopanib induced proteasomal degradation of YAP/TAZ. The sensitivities to these drugs are correlated with dependence on YAP/TAZ in breast cancer cell lines. Combinations of these compounds with each other or with other anti‐cancer drugs efficiently reduced cell proliferation of YAP/TAZ‐dependent breast cancer cells. These results suggest that these drugs can be therapeutics and chemosensitizers for YAP/TAZ‐dependent breast cancers.